Wind and solar assessment in the Sahelian Zone of Chad - Hassane, Abdelhamid Issa; Didane, Djamal Hissein; Tahir, Abakar Mahamat; Hauglustaine, Jean-Marie (Penerbit UTHM, 2018)
Renewable energy sources have long been renowned as potential sources of free, clean and inexhaustible energy. However, energy in Chad is still exploited from non-renewable sources due to lack of comprehensive wind and solar maps, skills and public awareness pertaining to its significance in the country. This study is therefore set out to provide assessments of both wind and solar energies in the Sahelian zone in Chad, using the statistical twoparameter Weibull distribution function and Angstrom-Prescott model, respectively for a ten-year period. The evaluation of wind potential shows that the annual mean of the shape and scale parameters for all stations under study varied in the range of 1.26 – 1.56 and 2.49 m/s – 3.91 m/s, respectively. Stronger wind speed was observed during the dry season and a relatively slower wind speed was perceived during the wet season. Among the four stations, N’Djamena showed the highest power density compared to the other three stations with a mean power density that ranges between 100 W/m2 – 220 W/m2 . The prediction of solar potential in this region indicates that the global solar radiation for all stations is promising with station Abeche however, to show the highest solar energy density on average. A good agreement between Angstrom model and NASA data was also observed.